Efeitos ambientais dos resíduos da pesca artesanal em Marataízes, Espírito Santo - Brumana, João Vitor da Silva (2024)
Artisanal fishing is a cornerstone of coastal communities in Espírito Santo, Brazil, providing a vital source of livelihood for numerous families. Its significance extends beyond economic aspects, encompassing cultural and social dimensions, forging a deep connection between communities and the environment. Despite its crucial role, the generation of waste from fish processing poses a significant challenge for the fishing sector. The current management of this waste is characterized by worrying irregularities, leading to substantial negative environmental impacts. This inadequate management not only jeopardizes the quality of marine ecosystems but also contributes to large-scale environmental manipulation. This research delves into the critical role of artisanal fishing in the environmental impacts associated with fishing activities in the municipality of Marataízes, Espírito Santo. The primary objective is to evaluate the environmental impacts resulting from the irregular disposal of waste from artisanal fishing in the Barra do Itapemirim and Pontal ports, located in the municipality of Marataízes. The methodology employed in this study integrates both qualitative and quantitative approaches. Initially, the evaluation of the artisanal fishermen's profile involved the application of questionnaires, following a documentary methodological approach. This stage encompassed aspects identified in the diagnosis, including the disposal of waste resulting from fish processing. To analyze the composition of the generated waste, physical, chemical, and nutritional characterizations were performed, providing a comprehensive understanding of the waste generated in the process. The results and analyses of this research enabled the characterization of the fishermen's profile and fishing activities in the studied communities. Furthermore, it was possible to understand the composition of fish waste, noting the significant presence of lipids, proteins, and energy. It was also identified that the continuous disposal of this waste is causing significant environmental impacts due to the high concentration of the parameters found. This made it possible to suggest measures for the reuse of this waste, such as the production of fishmeal, aiming to mitigate these impacts and promote a more sustainable use of available resources